Double-pass chirped bragg grating erbium-doped fiber amplifier: Improved transmission distance - Jamaludin M.Z.; Abdullah M.K.; Abdullah F.; Rahman F.A.; Mahdi M.A. (2023)
The paper discussed on experimental result that improve the transmission distance by use of an integrated dispersion compensated double-pass Erbium-doped Fiber Amplifier (DPCEDFA). The chromatic dispersion compensation is achieved using chirped fiber Bragg grating as part of the EDFA design. The eye-pattern, eye-opening and timing jitter obtained using this technique shows an improvement equivalent to the distance of about 50km compared with the conventional double-pass EDFA (DP-EDFA). 2008 IEEE.